Phenylketonuria in Western Libya: Demographic Patterns, Diagnostic Delays, and Neurodevelopmental Outcomes (Comprehensive Journal of Science, 2025)
Phenylketonuria (PKU) is a rare autosomal recessive metabolic disorder characterized by adeficiency in phenylalanine hydroxylase (PAH), leading to high concentrations ofphenylalanine in the blood which can cause brain damage. This research focuses onevaluating the demographic patterns of PKU in the western region of Libya and assessing theeffect of early intervention on neurodevelopmental outcomes. Data collection was done at ElGalaa Hospital and subsequently analyzed using SPSS. Early diagnosis and dietaryintervention to lower blood phenylalanine concentrations are crucial to help prevent thecognitive and behavioural complications that are associated with this disorder.
Keywords: Phenylketonuria; autosomal recessive; western region of Libya.